Epidemiological Profile of Pandemic Influenza A (H1N1) 2009 at Dhaka Medical College Hospital (Journal of Medicine, 2010)
The first case of 2009 pandemic influenza A (H1N1) virus infection in Bangladesh was documented on June 18. Subsequently, persons with suspected cases of infection and contacts of those with suspected infection were tested. Individuals in whom infection was confirmed were hospitalized and quarantined, and some of them were closely observed for the purpose of investigating the nature and duration of the disease. In Dhaka Medical College Hospital, there were 28 admitted patients in flu ward and 2335 registered suspected H1N1 influenza cases attended in flue corner but 833 highly suspected cases were recorded in case record form. We describe the epidemiological characteristics of 28 indoor (flu ward) and 833 outdoor (flu corner) patients. Most of them were in between 20 to 30 years age group. Among 833 outdoor patients 611(73.34%) were male and 222(26.65%) were female. 354 (42.49%) patients were student, 195 (23.40%) were service holder. No patients (indoor) had any serious underlying medical conditions. Keywords: Pandemic influenza A (H1N1), Dhaka Medical College Hospital, Bangladesh, epidemiology. DOI:10.3329/jom.v11i1.4259 J Medicine 2010: 11: 3-6